Public Service Motivation, Prosocial Motivation and Altruism: Towards Disentanglement and Conceptual Clarity. Issue 14 (26th October 2019) - Schott, Carina; Neumann, Oliver; Baertschi, Muriel; Ritz, Adrian
ABSTRACT: Research on public service motivation (PSM) has made great strides in terms of study output. Given the enormous scholarly attention on PSM, it is surprising that considerable conceptual ambiguities and overlaps with related concepts such as prosocial motivation, and altruism still remain. This study addresses this issue by systematically carving out the differences and similarities between these concepts. Taking this approach, this study clarifies the conceptual space of both PSM and the other concepts. Using data from semi-structured interviews with police officers, it is illustrated that PSM and prosocial motivation are different types of motivation leading to different types of prosocial behaviour.